Legal Protection from Provocate Abortion Againts the Child Conceived Because Rape (Case Study on Jurisdiction Ex Residency of Cirebon) - Eka Damayanti Damayanti; Aryani Witasari (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
The problems of this study are: view of the living norms of public life related to the legalization of abortion under PP No. 61 of 2014 on Reproductive Health in the jurisdiction of Ex Residency of Cirebon, Legal protection of children conceived for Pregnancy Preferred (KTD), form the legal protection of children conceived for Pregnancy Preferred (KTD), particularly rape victims in the future.The method used by researchers is sociological approach juridical law and specification in this study was included descriptive analysis. As for sources and types of data in this study are primary data obtained from interviews with field studies Cirebon MUI, and secondary data obtained from the study of literature. Data were analyzed qualitatively. The problems studied by the theory of effectiveness and progressive law.Based on the results of research that potentially incompatible with Islamic law if it does not pay attention to the provisions of law or the Fatwa of Indonesian Ulama Council, besides that government regulation is taking the authority of the judiciary by the executive branch, because the authority to determine a person can have an abortion only submitted to the doctor and known by the Health Department / districts forwarded to the Provincial Health Office, without having to get a judgment and / or determined by the court, including the MUI Fatwa can ignore. Abortion performed by a rape victim is allowed and does not constitute a crime, but as a special lex and Health Act Government Regulation No. 61 Of 2014 on Reproductive Health has taken over the authority of the judiciary, because abortion is performed by a rape victim does not need to get a determination from the court. Reflected Bill-September 2019-the Penal Code refers to the Law of Health and Government Regulation No. 61 of 2014 on Reproductive Health, so that the provision is contrary to the Constitution of the Republic of Indonesia 1945.Keywords: Provocate Abortion; Child; Rape; Legal Protection.